Teknik Mengembangkan Modul Mata Kuliah Sejarah Pendidikan Islam - ., Nisrokha (Madaniyah, 2015)
This research is the development of research is a study to produce a product in the form of modules History of Islamic Education in order to assist the student in learning the history of Islamic Education courses. The research objective of this development is to develop a module that is suitable for studying the course History of Islamic Education in improving the quality of learning outcomes. The module is designed to allow students to be able to study the History of Islamic Education courses independently and conventional. In developing modules ways researchers developed modules, the first step to do is to conduct a needs analysis, curriculum analysis and develop subject matter into modular teaching materials History of Islamic Education.